Migration, Migrants and Policy in the United Kingdom - Timothy J. Hatton; Stephen Wheatley Price (Institute for the Study of Labor (IZA), 1999)
This paper draws together, in the form of a survey, a number of different aspects of the United Kingdom?s international migration experience since the Second World War. The areas covered include changes in the volume and composition of international migration and the factors influencing migration; the background to, and the development of, restrictions on immigration; and the links between immigration policy and race relations. This is followed by an examination of the education and labour market status of immigrants and ethnic minorities as compared with native- born whites. Results from recent econometric research on wage and employment differentials are presented and interpreted in the wider context. Finally, the possible effects of migration on the economy at large are briefly discussed.
Keywords: J61; J15; 330; Migration; migration policy; Internationale Wanderung; Geschichte; Migrationspolitik; Ausländische Arbeitskräfte; Lohn; Arbeitsmarkt; Großbritannien